Aplikasi Sistem Forecasting CV. Karisma Motor Dengan Metode ARIMA - Reinaldo Andhika Halim; Alexander Setiawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2016)
CV. Karisma Motor is a private company that specialize in motorcycle selling and buying of one of well known brand in Indonesia. Up until now the forecasting process for stock buying from CV. Karisma Motor still does by using only estimeation based on past sales data. This makes buying process no fully effective because decision makings doesn’t have a firm ground. Therefore, to anticipate that problem a forecasting system is design so it can be used by CV. Karisma Motor to help decision making. The process for making this forecasting system is through a few step, the first step is to do a survey and need analysis, the second step is collecting sales data from the past year, the third step is creating flowchart and designing of entity relationship diagram, and then afterwadrs creating the database. Program creation is using Microsoft Visual Basic .NET 2010 for the programming languange and MySQL for the database, forecasting calculation is using ARIMA method. Based on system testing, the forecasting system can store goods data, calculate forecasting based on past sales data, store the result of forecasting that have been done, displays forecasting result that have been done before and error calculation to get smallest error value among three methods with average value from testing is 1,42.